Improving managers' intelligence through Systems Thinking. Issue 1 (12th April 2018) - Mella, Piero; Gazzola, Patrizia
Abstract : Purpose: Accepting the assumption that our intelligence depends on the ability to construct models which may allow us to acquire, update and transmit our knowledge, this paper aims to highlight the role of Systems Thinking in developing the "intelligence" of managers for all types and sizes of organization. Design/methodology/approach: Four relevant contributions for improving the "intelligence" of managers will be examined: the ability to understand and model dynamic systems, the structure of Control Systems, the rules of the decision-making process and the identification of systems archetypes. Findings: The paper will show that Systems Thinking, through the logic of Control Systems, offers managers a comprehensive representation of the problem-solving and decision-making processes, teaching them how to distinguish problems from symptoms and to acquire a leverage effect. Additionally, Senge's system archetypes will be presented and new archetypes will be added to Senge's list. Practical implications: The viability of every organization and its effective resilience and survival make it more than ever necessary for managers to adopt Systems Thinking, not only as a technique but also primarily as a discipline for efficient and effective thinking, learning, communication and explanation with regard to the dynamics of the world. Originality/value: The message of the paper is that by continually applying the rules and language of Systems Thinking, managers develop the capability to continually adapt their models to the dynamics of the world, increase their learning capacity and better gauge their consequent judgments, decisions and behavior, thereby removing the mental impediments to intelligence (inappropriate mental models, defensive routines, judgmental biases, rules, etc.).